2020
DOI: 10.1101/2020.10.05.325936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CEP78 functions downstream of CEP350 to control biogenesis of primary cilia by negatively regulating CP110 levels

Abstract: CEP78 is a centrosomal protein implicated in ciliogenesis and ciliary length control, and mutations in the CEP78 gene cause retinal cone-rod dystrophy associated with hearing loss. However, the mechanism by which CEP78 affects cilia formation is unknown. Based on a recently-discovered disease-causing CEP78 p.L150S mutation, we identified the disease-relevant interactome of CEP78. We confirmed that CEP78 interacts with the EDD1-DYRK2-DDB1VPRBP E3 ubiquitin ligase complex, which is involved in CP110 ubiquitinati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
6
1
Order By: Relevance
“…We found that CEP78 loss leaded to shortening of sperm flagellum, with Cp110 down-regulated in Cep78 -/- testis ( Supplementary Figure S5 ), which is inconsistent with Gonçalves et al’s findings that cells lacking CEP78 display up-regulated CP110 and reduced cilia frequency with long cilia phenotype[15]. It seems that Cep78 may regulate formation of sperm flagellum by a different mechanism.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…We found that CEP78 loss leaded to shortening of sperm flagellum, with Cp110 down-regulated in Cep78 -/- testis ( Supplementary Figure S5 ), which is inconsistent with Gonçalves et al’s findings that cells lacking CEP78 display up-regulated CP110 and reduced cilia frequency with long cilia phenotype[15]. It seems that Cep78 may regulate formation of sperm flagellum by a different mechanism.…”
Section: Discussioncontrasting
confidence: 91%
“…Deregulation of Cep78 is also associated with colorectal cancer[13], prostate cancer[14], and asthenoteratozoospermia[12]. As a centrosomal protein, CEP78 functions downstream of CEP350 to control biogenesis of primary cilia [15], and regulates centrosome homeostasis through interactions with other centrosomal proteins, including CEP76, CP110 and EDD-DYRK2-DDB1 VprBP [6]. Despite these findings, the biological function of Cep78, especially its function and mechanism in CRD with male infertility remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, centriolar satellites promote removal of CP110 from both RPE1 cells and MEFs, but are dispensable for ciliogenesis in MEFs, revealing that removal of all CP110 from mother centrioles is not a precondition for ciliogenesis in some cell types. Multiple roles for CP110, both promoting and inhibiting ciliogenesis, have previously been described ( Gonçalves et al, 2021; Walentek et al, 2016; Yadav et al, 2016 ). One possible explanation for the cell-type specificity of PCM1 function is that centriolar satellites remove CP110 from mother centrioles in all cell types, but different thresholds of CP110 reduction are required to initiate ciliogenesis in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple signi cant associations between 3 UTR methylation of CEP350 gene and sensitivity to chemotherapy in small cell lung cancer (SCLC) (42). Primary cilia are antennae-like sensory organs that play a key role in coordinating human development and tissue homeostasis signaling pathways (43) . CEP350, together with other molecules, directs the highly conserved intra agellar transport (IFT) protein complex into the cilia, participating in primary cilia assembly and signaling molecule transport (44).…”
Section: Discussionmentioning
confidence: 99%